THE LENGTH-WEIGHT RELATIONSHIP OF Butis sp. IN THE TAMBUN RIVER, TOLITOLI DISTRICT, CENTRAL SULAWESI - Suardi Laheng; Dwi Utami Putri; Febriani Febriani (Jurusan Perikanan dan Kelautan, 2024)
Butis sp. is a type of fish that possesses physical characteristics such as small scales and a yellowish belly. Information regarding the existence and growth of this type of fish is still limited to the Tambun River, Tolitoli Regency. Analyzing the length and weight of the fish is one of the methods used to determine the biological conditions and fish stocks, there by facilitating the management of biodiversity sustainability. The aim of this study was to determine the relationship between the length and weight of Butis sp. in order to understand fish growth patterns. This research was carried out for 2 months in Sungai Tambun, Tolitoli Regency, Central Sulawesi Province. The location for collecting sample were divided into 3 stations. The test parameters observed were the relationship between length and weight and habitat conditions. The research results of Butis sp. in Sungai Tambun, Tolitoli Regency showed a positive allometric growth pattern (b= 3,25). The water quality in the Tambun River still supports the growth of Butis sp. (temperature 25-28oC, pH 5,5-8,5).Keywords : Biodiversity, fish biology, growth, positive allometrics